2020
DOI: 10.1016/j.cub.2020.03.066
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature and Sweet Taste Integration in Drosophila

Abstract: Highlights d Flies find sweet foods less appealing if they are cool d Rejection of cool food requires bitter taste neurons and mechanosensory neurons d Bitter taste neurons and mechanosensory neurons in the fly tongue are cool activated d A rhodopsin is needed in a subset of bitter taste neurons for rejecting cool food

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…showed that Rh5 and Rh6 are coexpressed with TRPA1 in the body wall. A recent study identified that Rh6 and a different PLC, PLC21C, are necessary for the cool activation of adult bitter neurons [28]. If the function of Rh6 in cool sensing is conserved throughout the development, then the rhodopsin pathway, at the late third instar, drives an attractive behavior.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…showed that Rh5 and Rh6 are coexpressed with TRPA1 in the body wall. A recent study identified that Rh6 and a different PLC, PLC21C, are necessary for the cool activation of adult bitter neurons [28]. If the function of Rh6 in cool sensing is conserved throughout the development, then the rhodopsin pathway, at the late third instar, drives an attractive behavior.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…We prepared flies for the PER assays as described. 8 Briefly, we starved males for 2 hr for the assays, unless indicated otherwise, and trapped the animals in a cutoff pipet tip (Olympus 200 mL Reach Tip, 24-150RL) with only the labellum exposed. We water saturated the flies before stimulating them with the food (0.5 mL in volume) for $0.2-0.6 s on the labellum.…”
Section: Article Star+methodsmentioning
confidence: 99%
“…To monitor a fly's motivation to feed, we used the proboscis extension response (PER). 8,21 If the labellum is touched with an appealing food at the end of a probe, the animal will extend its proboscis in an attempt to feed. The interest in feeding increases with the starvation time.…”
Section: Particle Size Influences Food Appeal In Fliesmentioning
confidence: 99%
See 2 more Smart Citations